Peningkatan Suasana Akademis dalam Menghafal Al-Quran pada Malam Hari Di Gazebo Pondok Pesantren Menggunakan Lampu LED Berbasis Teknologi Sel Surya - Suwitno; Iswadi Hasyim Rosma; Murdiya, Fri; Sandhyavitri, Ari; Dian Yayan Sukma; Nurhalim; Firdaus (Jurnal Pengabdian UntukMu NegeRI, 2025)
Khairul Ummah 2 Islamic Boarding School, located on Jalan Gajah, Bambu Kuning Village, Tenayan Raya District, Pekanbaru City, is equipped with facilities such as a mosque, madrasah office, teachers’ housing, dormitories, gazebos, and learning spaces. However, lighting in the gazebo area is still inadequate, limiting its use at night. Through this community service project, a solar-powered lighting system was designed and installed to support nighttime activities, particularly Qur’an memorization. The system includes a 12V 30Ah battery module, a 12V–24V 30A solar charge controller (SCC), 12V 30-watt LED lamps, and a 100 Wp solar panel mounted on the gazebo roof. During the day, the battery is charged via the solar panel, and at night it powers the lamps. Four lighting units were installed and donated to the school. Post-installation, light intensity was measured using a fluxmeter, yielding results between 173–245 lux. This range complies with Indonesian National Standard (SNI 03-6575-2001), which recommends 120–250 lux for reading or working areas. The lighting system is expected to enhance the comfort of students’ nighttime activities, particularly Qur’an memorization, which is more effective in a calm and relaxed evening environment.